The Influence of Product Quality, Price, Brand Image, and Lifestyle on the Purchase Decision of Rabbani Hijabs (A Study of Junior High School Students in Purbalingga) - Zuraida, Maila; Widyaningtyas, Dian (PT FORMOSA CENDEKIA GLOBAL, 2025)
The study aims to analyze the influence of product quality, price, brand image, and lifestyle on the decision to purchase Rabbani hijabs among students at junior high school in Purbalingga, Indonesia. This study employs a purposive sampling technique involving 122 respondents. Data are analyzed using the Structural Equation Modeling - Partial Least Squares (SEM PLS) method to test the relationships between observed variables. The results of this study indicate that Product Quality, Brand Image, and Lifestyle have a positive and significant influence on Purchase Decisions. These findings provide insights into understanding the behavior of Muslim teenage girls as consumers, as well as practical benefits for producers and marketers in developing more effective strategies based on the factors influencing purchase decisions. This study can also serve as a reference for further research in the fields of marketing and consumer behavior.